DESIGN OF INTERACTIVE LEARNING MEDIA IN THE COVID-19 PANDEMIC TIME USING ISPRING - Ahmad Fadillah; Westi Bilda; Hairul Saleh; Yenni Yenni (Prima: Jurnal Pendidikan Matematika, 2021)
The learning process is a systematic activity deliberately designed by educators in order for the desired learning objectives to be achieved. One of the factors that affects the process of learning is a learning medium. Learning media is a tool that used by educators so that the concept or material to be delivered on target and meaningful for learners. This research was conducted at Universitas Muhammadiyah Tangerang in the mathematics education study program. The purpose of this research is to develop Ispring interactive media design. The methods used in this study are research and development with ADDIE (Analysis, Design, Development, Implementation, Evaluation) models. The stages include analysis, design, development, and implementation. Based on the validation results of the experts by getting scores of 80.34% and 80% respectively with proper criteria, and the results of small-scale trials got score of 85% and 88.34% respectively which was feasible and usable.